La Poste : pricing banking services - Baack, Daniel W., (SAGE knowledge. Cases., 2016)
The French postal service provider, La Poste, has expanded to become one of Europe's leading logistics, corporate services and financial providers. La Poste has been successful in France, Germany and the United Kingdom and, given this success, the company's leaders are looking to expand into other French-speaking nations. This case study asks readers to assess the various options open to La Poste, and to decide the right choice for the company's marketing and management teams.